ROLE OF ISOTRETINION IN CANCER PREVENTION AND MANAGEMENT IN MALIGNANCIES ASSOCIATED WITH XERODERMA PIGMENTOSUM - Zaman, Sajid; Gillani, Jawad A; Nabeela, Nabeela; Khattak, Rauf; Iqbal, Iqbal; Ain, Noor ul; Zanaib, Zanaib; Fayyaz, Fayyaz (Journal of Ayub Medical College Abbottabad, 2014)
We report a case of 15 year old female patient of xeroderma pigmentosum with large squamous cell carcinoma on the left side of cheek. She received combination chemotherapy with isotretinoin for a period of 4 months and showed complete clinical remission of tumour. The role of isotretinoin in cancer prevention and management of malignancies associated in xeroderma pigmentosum is also reviewed through literature. Keywords: Xeroderma pigmentosum, isotretinion, malignancies